Effectiveness of a peer support intervention for antenatal depression: a feasibility study. (26th May 2020) - Carter, Ruth; Cust, Fiona; Boath, Elizabeth
ABSTRACT: Objective: A feasibility study for a randomised controlled trial to assess the acceptability, recruitment, feasibility and effectiveness of a peer support intervention for women with antenatal depression. The key premise of peer support is based upon the trust and empathetic understanding engendered by common experiences. Method: Twenty pregnant women were recruited by their community midwife using the Whooley questionnaire at between 28–30 weeks' gestation to ascertain their level of mood and general mental health. Women identified as having potential antenatal depression were randomly assigned into a control group (routine care alone which includes contact with a midwife and in some case an obstetric Doctor with access to a GP if required) or intervention group (6-weekly visits from a peer support worker in addition to routine care). Participants from both the control and intervention group, and the Peer Support Workers (PSWs) were then interviewed at the end of the six-week period. All participants, and the PSW's, were also asked to keep log books during the trial to record their feelings and experiences. The results were then analysed using thematic analysis. Results: The analysis of qualitative data from the PSWs, and the participants in the intervention group, suggest the peer support intervention is acceptable, helpful and supportive to both pregnant women and, indeed, the PSWs. The women within the intervention group valued the peer support highly, reporting that being able to speak openly to a PSW meant that feelings of alienation, abnormality, isolation and stigma were replaced with social support, confidence, self-esteem and hope for recovery. The PSWs reported a positive impact upon their own wellbeing and a realisation that they had, indeed, moved forward with their lives. A proportion of the women randomised to the control group described feelings of disappointment and frustration with the lack of support currently available to them. Conclusion: This feasibility study suggests a full randomised controlled trial (RCT) is warranted given the high recruitment, adherence, and acceptability of the intervention to participants.